The Differential Enrichment Law of Tight Sandstone Gas in the Eighth Member of Shihezi Formation in the North and South of Ordos Basin - Haoyuan Wang; Jingong Zhang; Zishu Yong; Xiumei Qu (Energies)
Unconventional oil and gas resources are important energy sources for alleviating energy crises and maintaining sustainable social development. Therefore, the subsequent exploration and development of the basin summarizes and analyzes the reasons for the difference in natural gas enrichment between the southern and northern parts of the Ordos Basin. The tight sandstone gas of the Upper Paleozoic in the Ordos Basin has become a key field for increasing reserves and production of natural gas in the basin. As a high-quality tight sandstone gas reservoir, the eighth member of the Shihezi Formation only has good gas production in the south of the basin. For this reason, the types of natural gas source rocks in the north and south of the Upper Paleozoic were summarized, and the main types of gas source rocks in the north and south were clarified. The sedimentary facies of the eighth member of the Shihezi Formation and the Shanxi Formation were analyzed. The results show that the main gas-producing source rock in the northern part of the basin is coal rock, and in the southern part, it is dark mudstone. The Permian Shanxi Formation in the northern part of the basin mainly develops the delta front, which provides good conditions for the development of coal and rock. Compared with the northern Shanxi Formation, the Permian Shanxi Formation in the southern Ordos Basin mainly develops marine facies and marine-continental transitional facies, and the coal seam is not created. Therefore, the natural gas produced by the coal of the Shanxi Formation can easily migrate to the good reservoir in the eighth member of the box, which is also the reason for the difference in the enrichment of tight sandstone gas in the north and south of the Ordos Basin.